EFEKTIVITAS PENGGUNAAN APLIKASI QUIZIZZ UNTUK PENILAIAN PEMBELAJARAN - Fitriyeni; Wahyu Kurniawat (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This current condition requires educators to find out a solution in order to continue the learning assessment effectively. Quizizz is a game and multi-game-based educational application that makes an assessment by applying quizzes funnier because there are elements within the game. Hence, this application is effective to use in teaching and learning assessments. This article identifies the effectiveness of using the Quizizz application for studentlearning assessment. The research described in this article is a quantitative descriptive research by using research techniques using questionnaires. The research subjects involved 34 students of PGSD UPY class A3 - 2021. Assessment is an obligation for teachers that must be conducted in teaching and learning. The assessment is aimed to see how far the successful learning and its obstacle are. Therefore, the assessment can be used as improvement and feedback in the improvement of the teaching and learning process. Thus, the result of this research showed that the average percentage of effectiveness was Strongly Agree (SS) 23.86%, Agree (S) 41.37%, Moderately Agree (CS) 22.47%, Disagree (TS) 6.42%, Strongly Disagree Agree (STS) 1.83%